ANALYSIS OF THE INFLUENCE OF TACTICS ON THE EFFICIENT USE OF PLAYING SPACE IN UNIVERSITY SOCCER - Simoes, Luis da Silva (Seven Editora, 2026)
Research on tactics and playing space management in football is fundamental, considering the current limitations in developing players who possess a deep understanding of the game and the ability to apply it effectively. One of the main difficulties faced by coaches is the lack of effective methods for teaching game tactics and strategies in an engaging and understandable way. In response to this need, researchers have developed innovative tools, including small educational games designed for specific objectives, such as developing game vision and improving decision-making on the field. These games have the potential to make training more attractive and effective, increasing players’ enjoyment and motivation to train, and consequently improving their performance on the field. One of the main issues in football is the difficulty in ensuring the effectiveness of tactics and the efficient management of playing space, despite the existence of various tactical variations. This is because the simple application of these tactics does not ensure effective learning and efficient player movement, raising the need for innovative methods that can overcome these limitations. This article investigates how soccer tactics, particularly those related to player movement, impact the effective management of playing space and seeks to identify, in the literature, movement patterns that can optimize team performance in matches. Given the importance of overcoming current limitations in teaching the application of tactics and management of playing space, this study will adopt an innovative approach, inspired by research that uses games to teach soccer, adapting it to programmed training and evaluations in Tactiup, with the aim of improving team performance in university competitions. To verify existing tactics, we conducted a systematic literature review, including scientific articles and books that addressed the topic of soccer tactics and management of playing space. We used specific inclusion and exclusion criteria to select the sources, including the relevance of the topic and the methodological quality of the studies. In addition, we used the Tactiup software to evaluate soccer tactics and analyze the results. The training sessions were held on the field of the Federal University of Bahia, where players participated in specific movement and playing space management exercises, using balls, cones, and vests. The training sessions were conducted over 8 non-consecutive weeks, with 2 sessions per week, generally on weekends, with scheduled games in national and regional university competitions. Players were evaluated before and after training to verify performance improvements. The study results showed that the training regimen led to a positive change in team performance. In particular, 75% of the team reported a change in behavior, which translated into improved positioning and attacking and defensive skills. Furthermore, the team showed a 70% reduction in goals conceded compared to previous competitions. These results were corroborated by positive player feedback and the team’s qualification for the finals of regional championships and national tournaments. Based on the results obtained, which showed a significant improvement in team performance, it is crucial that coaches focus on learning new training methods to teach players the key fundamentals of the game more effectively. This contributes to the development of football in Brazil through partnerships between training centers and specialized universities, aiming for the continued growth and development of football in the country, with better-prepared players and coaches.